1998
DOI: 10.1080/j.1600-0412.1998.770903.x
|View full text |Cite
|
Sign up to set email alerts
|

Vertical transmission of HCV

Abstract: Mother-to-infant transmission of HCV is possible only in the case of HCV-RNA positive mothers. In our study the rate of transmission is 3.6%, (2/56 babies with HCV-RNA positive mothers). HCV transmission may occur without evident association with breast-feeding or vaginal delivery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 0 publications
2
11
0
Order By: Relevance
“…[24][25][26][34][35][36][37][38]44,48,49 Between infants delivered vaginally versus by Cesarean section, overall rates of mother-to-infant transmission were similar. For vaginal delivery and Cesarean section respectively, the weighted rate of mother-to-infant transmission was 4.3% and 3.0% (crude rate 6.7%, SD ϭ 0.7% and 6.8%, SD ϭ 1.2% respectively).…”
Section: Mode Of Deliverymentioning
confidence: 71%
See 2 more Smart Citations
“…[24][25][26][34][35][36][37][38]44,48,49 Between infants delivered vaginally versus by Cesarean section, overall rates of mother-to-infant transmission were similar. For vaginal delivery and Cesarean section respectively, the weighted rate of mother-to-infant transmission was 4.3% and 3.0% (crude rate 6.7%, SD ϭ 0.7% and 6.8%, SD ϭ 1.2% respectively).…”
Section: Mode Of Deliverymentioning
confidence: 71%
“…Although mother-to-infant transmission occurred across a wide range of maternal viral titers, in 9 studies statistically higher maternal viral titers corresponded to a greater tendency for mother-to-infant transmission 19,33,34,40,[42][43][44][45][46] ; in 9 studies there was no difference. 18,20,27,[35][36][37][38][39]41 Most studies reported mother-to-infant transmission at viral titers beyond the range of 10 5 to 10 6 copies/mL. In one study higher levels of maternal serum HCV RNA also tended to correlate with higher colostrum levels of HCV RNA.…”
Section: Maternal Viral Titermentioning
confidence: 97%
See 1 more Smart Citation
“…Studies examining the mode of delivery have had conflicting results, with some showing a lower risk of vertical spread with Cesarean delivery 14,18,43 , while others noted no difference in transmission rates when Cesarean delivery was utilized 40,41 . Detection of viral RNA in children within 3 days of birth suggests that at least some cases of vertical transmission occur in utero 42 . Thus, it is not at all clear that performing an elective Cesarean delivery will reduce vertical transmission of hepatitis C virus.…”
Section: Discussionmentioning
confidence: 99%
“…A second reason is the risk of vertical transmission. Most authors have found few or no cases of infected children when their mothers had negative or low hepatitis C RNA titers, but significantly greater risks of an affected child in women with high RNA titers on quantitative PCR testing 14,[16][17][18][39][40][41][42][43] . Infants infected with hepatitis C during pregnancy or childbirth have been reported to develop severe clinical hepatitis, jaundice or death 39 .…”
Section: Discussionmentioning
confidence: 99%